Docetaxel and gemcitabine combination, as first-line treatment, in patients with extensive disease small-cell lung cancer. A phase II study of the Hellenic Cooperative Oncology Group - Skarlos, D.-V.; Dimopoulos, A.-M.; Kosmidis, P.; Papakostas, P.; N. Pavlidis; Bacoyiannis, C.; Kiamouris, C.; Klouvas, G.; Gogas, H.; Fountzilas, G.; Samantas, E. (Lung Cancer, 2003)
There is some evidence that taxanes and gemcitabine are effective antitumor agents against small-cell lung cancer (SCLC). A total of 20 chemotherapy-naive patients with extensive disease (ED) SCLC, were treated as a part of the first step of a phase II study, with docetaxel 50 mg/m2 and gemcitabine 1000 mg/m2, both administered on day 1 and 8 every 3 weeks up to a total of six cycles. For patients who progressed after the first cycle or had stable disease after the second cycle of chemotherapy, protocol treatment was stopped and further treatment with the standard cisplatin or carboplatin-etoposide combination was administered. Patients were in the vast majority male smokers with a good performance status. A total of 72 cycles was delivered while patients managed to receive the 78 and 84% of the planned dose of docetaxel and gemcitabine, respectively. Only six patients responded partially and the trial ended prematurely since at least seven responses were required among the first 19 patients. With a median follow-up of 13 months, median time to progression (TTP) was 8 months and median survival 9.6 months. Hematological and non-hematological toxicity was generally acceptable while patients tolerated their treatment reasonably well. In conclusion, docetaxel-gemcitabine showed a modest response rate in chemotherapy-naive patients with ED SCLC. © 2003 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: Docetaxel; Extensive small cell lung cancer; Gemcitabine